Translation and cross-cultural adaptation of the Educational Technology Device Predisposition Assessment into Brazilian–Portuguese language. Issue 3 (30th January 2021) - Braccialli, Ana Carla; Araújo, Rita de Cássia Tibério; Scherer, Marcia
Abstract: Objective: The study aimed to translate and culturally adapt the Brazilian–Portuguese version of the instrument Educational Technology Device Predisposition Assessment in its Brazilian version for the student and version for the teacher. Method: It is a methodological study, focusing on the steps for preparing an adapted version of the assessment instruments. The following operational system was adopted: 1st) initial and reconciled translation into Brazilian–Portuguese language; 2nd) back-translation and adequacy of the instrument; 3nd) equivalence analysis of the instruments' items; 4nd) Pretest and cultural adequacy. Result: The translated and culturally adapted version has a high index of agreement and good acceptability by the study participants. Conclusion: The translated and adapted to Brazilian Portuguese instrument can be used in the Brazilian school settings to verify the predisposition to use technologies. Implications for rehabilitation: Educational technologies enable students with many types of disability to receive instruction according to their learning needs and styles, assist them in communicating and participating more effectively, and increases self-confidence and motivation through the mastery of an educational program. Not all students benefit from the same type of educational technology and it is important to match them with the ones most appropriate for their use. The Educational Technology Predisposition Assessment assists in the selection of educational technologies based on a particular student's learning style, needs and preferences. The Educational Technology Predisposition Assessment is a validated measurement and it has been translated for use in Brazil and has been found to be a reliable tool.